Estado e “Poder Paralelo”: dois mundos separados por uma linha tênue - Silva, Elisabeth Maria de Mendonça (2021)
As the Brazilian news itself has frequently shown in recent years, there is an increasing - and increasingly notable - space and power of action by criminal organizations, which has also been called ―Parallel Power‖ - which is due to the fact that its structure and organization follow those found in the official state. They include the fact that they have an armed force, that they maintain a military power through which the social life of an entire territory is controlled by imposing rules of conduct, that they carry out welfare actions normally carried out by the State, that they directly or indirectly in the choice of local leaders, to also be characterized by the existence of an organizational bureaucracy and, of course, to assert themselves as a power, regardless of their formal non-recognition by the State, to which they are opposed. Taking these specificities into account, the present study had the general objective to understand, in the light of the theory found in the Philosophy of Law, what are and how the factors that contribute to the criminal organizations that constitute a ―Parallel Power‖ are processed - more particularly, those that are configured as criminal factions, among which we highlight the First Command of the Capital (PCC) - have been gaining more and more space and legitimacy within society, to the detriment of the scope and legitimacy that should be constitutive of the Public Power, exclusively . For that, we used the theoretical contributions of several authors, among which we highlight Kelsen, Rawls, Žižek, Habermas, Bourdieau, Weber, Bobbio, Cicco and Gonzaga, Freyre, Holland, DaMatta, Becker, Lévinas, Merton, Goffman and Feltran as the most recurring. As an object of analysis that both guided the delimitation of the theoretical tool and was also delimited by it, we reached a total of six publications extracted from the Folha de S.Paulo newspaper in the interval of the last six years, in which, according to the adopted methodological criteria, we find the expression ―parallel power‖ in approaches that talked about practices - real - related to these organizations. In addition to other publications and studies whose events portrayed were also articulated with the theory in this research, we were able to deepen the proposed understanding, concluding that, among the main factors that enable this reach and this legitimacy of the ―Parallel Power‖ in an increasing character, the most preponderant seems to understand precisely the set in which we witness the decadence of the State of Brazil due to its inefficiency in the provision of services that it has legally committed to provide, due to the slowness in solving the natural conflicts of social coexistence, its non-compliance with the law (and / or its application in a different way among Brazilian citizens), for the discredit of its members and employees (constantly involved in cases of corruption or influence peddling) and, mainly, for its structuring and organization aimed at serving one or more social strata that they represent the political and economic domain, to the detriment of social class and eco nomically more discredited. In the set of all the factors analyzed, the study undertaken leads us to believe, finally, that the exchange between the Public Power and the ―Parallel Power‖ has already taken place, so that the line of separation between these two worlds - which was tenuous, almost imperceptible - it ceases to exist at all, making it practically impossible to distinguish one from the other